THE EFFECT OF FINANCIAL PERFORMANCE, CAPITAL STRUCTURE AND MANAGERIAL OWNERSHIP ON COMPANY VALUE IN NON-CYCLICALS CONSUMER SECTOR COMPANIES LISTED ON THE IDX - Sultan Fadlullah Nuri; Rico Nur Ilham; Chairil Akhyar; Ristati (PT. Radja Intercontinental Publishing, 2024)
This research aims to analyze the influence of financial performance (NPM), capital structure (DAR), and managerial ownership (KM) on company value as measured by Tobin's Q in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (BEI) for the period 2019-2023 period. The research sample consisted of 10 companies selected based on data available on the official IDX website. The method used for data analysis is panel data regression with the help of the E-Views 12 application. The research results show that financial performance (NPM) has a positive and significant effect on company value (Tobin's Q), which indicates that the higher the company's profit margin, the higher as well as the market value of the company. Apart from that, capital structure as measured by (DAR) also has a positive and significant effect on firm value (Tobin's Q), which shows that the use of debt can increase firm value through the leverage effect. On the other hand, managerial ownership (KM) does not have a significant effect on firm value (Tobin's Q), which shows that even though managers own company shares, this factor is not strong enough to influence the assessment of firm value. Overall, the findings of this research confirm that financial performance and capital structure have a positive and significant influence on company value, while managerial ownership does not have a significant influence in the context of companies in the non-cyclical consumer sector listed on the BEI.